Lithium intercalation compound dramatically influences the electrochemical properties of exfoliated MoS2 - Ambrosi, Adriano (2015)
MoS2 and other transition metal dichalcogenides (TMDs) have recently gained a renewed interest due to the interesting electronic, catalytic, and mechanical properties which they possess when down-sized to single or few layer sheets. Exfoliation of the bulk multilayer structure can be achieved by a preliminary chemical Li intercalation followed by the exfoliation due to the reaction of Li with water. Organolithium compounds are generally adopted for the Li intercalation with n-butyllithium (n-Bu-Li) being the most common. Here, the use of three different organolithium compounds are investigated and compared, i.e., methyllithium (Me-Li), n-butyllithium (n-Bu-Li) and tert-butyllithium (t-Bu-Li), used for the exfoliation of bulk MoS2. Scanning transmission electron microscopy (STEM), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), and cyclic voltammetry (CV) are adopted for a comprehensive characterization of all materials under investigation. In addition, catalytic properties towards the hydrogen evolution reaction (HER) and capacitive properties are also tested. Different organolithium compounds exhibit different extent of Li intercalation resulting in different degrees of exfoliation. The inherent electrochemical behavior of MoS2 consisting of significant anodic and cathodic peaks as well as its capacitive behavior and catalytic properties towards hydrogen evolution reaction are strongly connected to the exfoliation compound used. This research significantly contributes to the development of large-scale synthesis of electrocatalytic MoS2-based materials.